Functionalized aliphatic polyketones with germicide activity. Issue 54 (9th December 2022) - Araya-Hermosilla, Esteban; Parlanti, Paola; Gemmi, Mauro; Mattoli, Virgilio; Di Pietro, Sebastiano; Iacopini, Dalila; Granchi, Carlotta; Turchi, Barbara; Fratini, Filippo; Di Bussolo, Valeria; Minutolo, Filippo; Picchioni, Francesco; et al.
Abstract : Surfaces coated by polyketones bearing quaternary ammonium compounds showed excellent bactericidal properties with antibacterial rate of 99%. Abstract : The COVID-19 pandemic has further confirmed to the community that direct contact with contaminated surfaces and objects represents an important source of pathogen spreading among humans. Therefore, it is of paramount importance to design effective germicidal paints to ensure a rapid and potent disinfectant action of surfaces. In this work, we design novel germicide polymeric coatings by inserting quaternary ammonium and sugar groups on the macromolecular backbone, thus respectively endowing the polymer with germicide features and hydrophilicity to interact with the surfaces. An aliphatic polyketone was selected as a starting polymer matrix that was functionalized with primary amine derivatives via the Paal–Knorr reaction. The resulting polymers were deposited on cellulose filter papers and checkboard charts with excellent coating yield and substrate coverage as determined by scanning electron microscopy for cellulose. Remarkably, the substrates coated by the functional polymers bearing quaternary ammonium compounds showed excellent bactericide properties with antibacterial rate of 99% and logarithmic reduction of >3. Notably, the polymers with higher hydrophobicity showed better retention on the substrate after being treated with water at neutral pH.